Generalized vitiligo in a dog with primary hypoadrenocorticism. Issue 5 (23rd June 2015) - Malerba, Eleonora; Morini, Maria; Fracassi, Federico
<x xml:space="preserve">Abstract</x> Background Vitiligo is presumed to be an autoimmune disorder in the dog; primary adrenal insufficiency (Addison's disease) is associated with immune‐mediated destruction of the adrenal cortex. Hypothesis/Objectives In this case report we describe a dog with primary hypoadrenocorticism that developed generalized vitiligo. Case report A 4‐year‐old spayed female cross‐bred dog developed signs of Addison's disease and this was confirmed by biochemical testing; the dog was treated with fludrocortisone acetate and then desoxycorticosterone pivalate. Three months after the diagnosis, the dog developed depigmentation of the whole hair coat and of several focal areas of the skin. Histopathological findings were consistent with vitiligo. Conclusions and clinical importance Dogs with immune‐mediated disease may develop other manifestations of immune‐mediated disease, including a combination of Addison's disease and vitiligo. The cause in this case was not determined.